(untitled) (ENTHYMEMA, 2024)
Starting from Childhood in the diorama, this paper investigates the connection between the fascination of dioramas presenting animals in their reconstructed habitat and writing as the active pivot around which Grünbein’s poetics of childhood revolves in relation to the disenchantment of the adult world. Parallels between the disillusioned grandparents – one of whom had worked at the Dresden slaughterhouse — and their not yet literate grandson are analysed in the light of the identification with the animal. Through poetic writing the child redeems an idea of truth and reality, already expressed by Baudelaire, as a representation of the internal experiences of the subject trying to repair all the senseless pain inflicted by man on animals. The way Grünbein addresses the child in the reader, capable of compassion and identification with those creatures, which had no voice and still have no voice, captures one of the most distinctive and structuring features of Grünbein’s poetics.